Complementary and alternative medicine use in children with thalassaemia. Issue 5 (21st August 2012) - Efe, Emine; Işler, Ayşegül; Sarvan, Süreyya; Başer, Hayriye; Yeşilipek, Akif
<x xml:space="preserve">Abstract</x> Aims and objectives. The aims of this study were to: (1) determine the types of complementary and alternative medicine use among children with thalassaemia as reported by parents and (2) describe sociodemographic and medical factors associated with the use of such treatments in families residing in southern Turkey. Background. Thalassaemia is one of the most common human genetic diseases. Despite the therapeutic efforts, patients will encounter a variety of physical and psychological problems. Therefore, the use of complementary and alternative medicines among children thalassaemia is becoming increasingly popular. Design. This is a descriptive study of complementary and alternative medicine. Methods. This study was conducted in the Hematology Outpatient Clinic at Akdeniz University Hospital and in the Thalassemia Centre at Ministry of Health Antalya Education and Research Hospital, Antalya, Turkey, between January 2010–December 2010. Parents of 97 paediatric patients, among 125 parents who applied to the haematology outpatient clinic and thalassaemia centre between these dates, agreed to take part in the study with whom contact could be made were included. Data were collected by using a questionnaire. Results. The proportion of parents who reported using one or more of the complementary and alternative medicine methods was 82·5%. Of these parents, 61·8% were using prayer/spiritual practice, 47·4% were using nutritional supplements and 35·1% were using animal materials. Conclusion. It was determined that a significant portion of the parents using complementary and alternative medicine use it to treat their children's health problems, they were informed about complementary and alternative medicine by their paediatricians and family elders, and they have discussed the use of complementary and alternative medicine with healthcare professionals. Relevance to clinical practice. To sustain medical treatment and prognosis of thalassaemia, it is important for nurses to consult with their patients and parents regarding the use and potential risks of some complementary and alternative medicine.